Implementasi Kebijakan Penyelenggaraan Kartu Asuransi Nelayan di Dinas Pertanian dan Perikanan Kota Medan - Ira Dwi Hastuti; Mujahiddin Mujahiddin (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this study was to determine the implementation of policies for the implementation of fisherman insurance cards at the Department of Agriculture and Fisheries in Medan City. Data collection techniques through interviews. From the research results obtained; The implementation of the Regulation of the Minister of Maritime Affairs and Fisheries Number 16 of 2016 concerning fisherman cards in article 6 states that the ministry and local governments organize fisherman cards as part of the implementation of duties and functions in the protection and empowerment of fishermen. The Department of Agriculture and Fisheries of Medan City has carried out its authority in accordance with the regulation of the Minister of Maritime Affairs and Fisheries Number 16 of 2016. The fisherman card is expected to be able to have an impact on the lives of fishermen. and fisherman cards, so that fishermen are only limited to having a fisherman's card